Complex collective dynamics of active torque-driven colloids at interfaces. (February 2016) - Snezhko, Alexey
Abstract: Modern self-assembly techniques aiming to produce complex structural order or functional diversity often rely on non-equilibrium conditions in the system. Light, electric, or magnetic fields are predominantly used to modify interaction profiles of colloidal particles during self-assembly or induce complex out-of-equilibrium dynamic ordering. The energy injection rate, properties of the environment are important control parameters that influence the outcome of active (dynamic) self-assembly. The current review is focused on a case of collective dynamics and self-assembly of particles with externally driven torques coupled to a liquid or solid interface. The complexity of interactions in such systems is further enriched by strong hydrodynamic coupling between particles. Unconventionally ordered dynamic self-assembled patterns, spontaneous symmetry breaking phenomena, self-propulsion, and collective transport have been reported in torque-driven colloids. Some of the features of the complex collective behavior and dynamic pattern formation in those active systems have been successfully captured in simulations. Graphical abstract: Highlights: Torque-driven colloids are novel promising active systems. Unconventional dynamic patterns, self-propulsion, and collective transport have been reported. Hydrodynamic interactions play a crucial role in the dynamics of active torque-driven colloids.